Manajemen Menu untuk Meningkatkan Profitabilitas di Seasalt Restaurant, Alila Seminyak - Putu Ayu Pande Octaviana; I Nyoman Sudiksa; I Putu Utama (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2020)
Seasalt Restaurant is the main food and beverage sales outlet in Alila Seminyak. In 2018, Seasalt Restaurant, the main food and beverage outlet did not achieve the profit target set by management. In addition, the actual cost of basic food raw materials exceeds the basic food raw material prices. This condition requires menu management to optimize food sales in restaurants, so as to get maximum income. This study aims to determine the classification of food menus in 2018 and determine the menu management to increase profitability. This study used quantitative analysis techniques using menu engineering approach by analyzing the level of popularity, profitability, menu classification and analyzing menu management through interviews. It was concluded that out of 75 menu items, there were 14 menu items in Star classification, 22 menu items in Plow horse classification, 18 menu items in Puzzle menu classification and 21 menu items in the Dog menu classification. Future studies are expected to test other factors that affect profitability, especially in restaurants.